Definitive treatment in squamous cell carcinoma of head and neck: A retrospective analysis of chemoradiotherapy in a university hospital setting - Hádila Silva Veras Sousa; Vivian Naomi Horita; Davi Magalhães Leite Novaes; Matheus Yung Perin; Daniel Naves Araújo Teixeira; Joyce Gruenwaldt; Eduardo Baldon Pereira; Carlos Takahiro Chone; Gustavo Jacob Lourenço; Ligia Traldi Macedo; Carmen Silvia Passos Lima (Brazilian Journal of Otorhinolaryngology)
Objective: To evaluate toxicities, tumor control, Event-Free Survival (EFS) and Overall Survival (OS) of patients with locoregionally advanced Head and Neck Squamous Cell Carcinoma (HNSCC) treated with definitive platinum-based Chemoradiation (CTRT). Methods: A total of 233 patients underwent treatment with RT plus weekly or every three weeks Cisplatin (CDDP) or Carboplatin (Carbo). Toxicity and response to treatment were classified using conventional criteria. Kaplan-Meier, log-rank test, and Cox regression (univariate and multivariate) were used to assess patient survival. Results: Half of patients presented toxicities grade 3 or 4, with nausea/vomiting and nephrotoxicity being more common in RT and CDDP group and anemia and neutropenia in RT and Carbo group. Complete or partial response was observed in 75% of patients, and the distinct protocols did not alter the treatment response. Two-year EFS and OS probabilities were 43.3% and 66.0%, respectively. Active smoking, an ECOG score of 2 or higher, stage IV tumor, and treatment with RT and Carbo were independent prognostic factors for poorer outcomes. Patients of these groups had approximately double chance of relapse and progression to death compared to others. Conclusion: Our data indicate definitive treatment with RT and CDDP as the best treatment for locoregionally advanced HNSCC treated in Brazilian public hospitals. However, prospective randomized studies are required to establish the ideal treatment for those patients. Level of evidence: 3.